Phase II trials of rhizoxin in advanced ovarian, colorectal and renal cancer. - Kerr, D. J. (Nature Publishing Group, 1995)
Rhizoxin is a tubulin-binding anti-neoplastic agent which is active in a range of murine tumour models. The recommended schedule, of intravenous (i.v.) bolus administration at a dose of 2 mg m-2 every 3 weeks, has been assessed in three phase II trials of ovarian, renal and colorectal cancer. In general terms the drug was fairly well tolerated, but the response rate was disappointing: 0/18, colorectal cancer; 0/18, renal cancer; 1 partial response (PR)/17, ovarian cancer.